Inflammation-driven periostin in ECRS has contrasting effects on tissue structural integrity and osteitis - Kim, Soo-In; Rha, Min-Seok; Kim, Jinsun; Ahn, Sang Hyeon; Ryu, Ji-Hwan; Cho, Hyung-Ju; Kim, Chang-Hoon (Frontiers in Immunology, 2025)
IntroductionEosinophilic chronic rhinosinusitis (ECRS) is a severe form of chronic rhinosinusitis characterized by type 2 inflammation, tissue remodeling, and bone thickening, known as osteitis. Periostin, a matricellular protein involved in extracellular matrix (ECM) regulation and T helper 2 (Th2)-mediated inflammation, is markedly elevated in patients with ECRS; however, its pathophysiological role remains unclear.MethodsWe investigated the role of periostin in inflammation and tissue remodeling in ECRS using samples from ECRS patients, human nasal epithelial cells and fibroblasts, as well as an ECRS mouse model including periostin knockout mice.ResultsPeriostin levels were elevated in ECRS tissues and modestly correlated with osteitis scores. Th2 cytokines increased periostin expression, particularly in nasal fibroblasts. Conditioned medium containing periostin promoted osteogenic differentiation in vitro, whereas neutralizing antibodies reduced the expression of osteogenic markers. In an ECRS mouse model, periostin deficiency led to reduced bone thickening and lower expression of osteogenic markers despite similar eosinophil infiltration. Furthermore, periostin-deficient mice exhibited greater epithelial collapse and reduced fibronectin levels, indicating compromised ECM integrity.DiscussionThese findings demonstrate that periostin contributes to osteogenesis and maintenance of structural stability in the inflamed sinonasal mucosa. Periostin may be a potential therapeutic target for controlling chronic inflammation and tissue remodeling in ECRS.